Early Trade-offs and Top-Level Requirement Definition for Antarctic Greenhouses - Bamsey, Matthew; Zabel, Paul; Zeidler, Conrad; Vrakking, Vincent; Schubert, Daniel; Kohlberg, Eberhard; Stasiak, Michael; Graham, Thomas (46th International Conference on Environmental Systems, 2016)
Germany Canada German Aerospace Center (DLR) Alfred Wegener Institute (AWI) University of Guelph 204 ICES204: Bioregenerative Life Support Vienna, Austria The 46th International Conference on Environmental Systems was held in Vienna, Austria, USA on 10 July 2016 through 14 July 2016. Matthew T. Bamsey, German Aerospace Center (DLR), Germany Paul Zabel, German Aerospace Center (DLR), Germany Conrad Zeidler, German Aerospace Center (DLR), Germany Vincent Vrakking, German Aerospace Center (DLR), Germany Daniel Schubert, German Aerospace Center (DLR), Germany Eberhard Kohlberg, Alfred Wegener Institute for Polar and Marine Research, Germany Michael Stasiak, University of Guelph, Canada Thomas Graham, University of Guelph, Canada The development of plant production facilities for extreme environments presents challenges not typically faced by developers of greenhouses in more traditional environments. Antarctica represents one of the most inhospitable environments on Earth and presents unique challenges to facility developers with respect to environmental regulations, logistics, waste management, and energy use. The unique challenges associated with plant production in Antarctica heavily influence the selection of subsystem components and technologies as well as the operational paradigms used to operate the facilities. This paper details a wide array of the early design choices and trade-offs that have arisen in the development of Antarctic plant production facilities. Specific requirements and several guidelines stemming from the Antarctic Treaty’s Protocol on Environment Protection and their influence on Antarctic plant production facilities are described. A review of guidelines for Antarctic greenhouses published by several national Antarctic operators is also described. The specific technology choices of several past and present Antarctic greenhouses are summarized, as are the general operational strategies, such as solid and nutrient solution waste handling. Specific lessons ...